2000
DOI: 10.1038/35012626
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of RAGE–amphoterin signalling suppresses tumour growth and metastases

Abstract: The receptor for advanced glycation end products (RAGE), a multi-ligand member of the immunoglobulin superfamily of cell surface molecules, interacts with distinct molecules implicated in homeostasis, development and inflammation, and certain diseases such as diabetes and Alzheimer's disease. Engagement of RAGE by a ligand triggers activation of key cell signalling pathways, such as p21ras, MAP kinases, NF-kappaB and cdc42/rac, thereby reprogramming cellular properties. RAGE is a central cell surface receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
1,095
4
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,123 publications
(1,124 citation statements)
references
References 24 publications
17
1,095
4
8
Order By: Relevance
“…4). A similar role for RAGE in mediating HMGB1 functional activities has been demonstrated in different models, including regeneration of peripheral nerves [38,62] and tumor growth/metastasis [63].…”
Section: Discussionsupporting
confidence: 56%
“…4). A similar role for RAGE in mediating HMGB1 functional activities has been demonstrated in different models, including regeneration of peripheral nerves [38,62] and tumor growth/metastasis [63].…”
Section: Discussionsupporting
confidence: 56%
“…We and others have shown that ERK activity increases as early as 0.5 to 1 h after ischemia in the middle cerebral artery territory (Alessandrini et al, 1999;Wu et al, 2000). This signaling is potentially linked to TLR2, TLR4, and/or RAGE activation (Ishihara et al, 2003;Park et al, 2003;Taguchi et al, 2000) and is known to promote transcription of cytokines such as TNFa (Fiuza et al, 2003). Tumor necrosis factor a mRNA reportedly increases within 1 h after induction of ischemia in the periinfarct and infarct area, peaks at 12 h, and remains elevated for up to 24 h (Gregersen et al, 2000;Lambertsen et al, 2002Lambertsen et al, , 2005Schroeter et al, 2003;Yang et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Membrane-associated HMGB-1 mediates cellular proliferation and growth by signaling through the receptor for advanced glycation end products (RAGE) (13). Interaction of HMGB-1 with RAGE activates intracellular signal transduction through mechanisms involving nuclear factor B (NF-B), mitogen-activated protein (MAP) kinases, plasminogen activation, Cdc42, and Rac (11,13).…”
Section: Hmgb-1 As a Nuclear Dna Binding Protein And Membrane-associamentioning
confidence: 99%